2021
DOI: 10.3389/fphys.2021.661413
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Dominant-Negative Effect of an SCN5A Brugada Syndrome Variant

Abstract: Loss-of-function mutations in the cardiac Na+ channel α-subunit Nav1.5, encoded by SCN5A, cause Brugada syndrome (BrS), a hereditary disease characterized by sudden cardiac death due to ventricular fibrillation. We previously evidenced in vitro the dominant-negative effect of the BrS Nav1.5-R104W variant, inducing retention of wild-type (WT) channels and leading to a drastic reduction of the resulting Na+ current (INa). To explore this dominant-negative effect in vivo, we created a murine model using adeno-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In particular, they systemically injected adeno-associated viral vectors carrying the human mutated SCN5A gene. Overexpression of R104W channels in vivo induced lowered heart rate, dramatic reduction of I Na current, prolonged RR intervals, and longer P-wave duration, indicative again of the dominant-negative effect observed previously in vitro [225].…”
Section: Brugada Syndrome: Modeling a Rhythm Disorder With Still Incompletely Defined Etiologysupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, they systemically injected adeno-associated viral vectors carrying the human mutated SCN5A gene. Overexpression of R104W channels in vivo induced lowered heart rate, dramatic reduction of I Na current, prolonged RR intervals, and longer P-wave duration, indicative again of the dominant-negative effect observed previously in vitro [225].…”
Section: Brugada Syndrome: Modeling a Rhythm Disorder With Still Incompletely Defined Etiologysupporting
confidence: 63%
“…Through these different models, it was possible to confirm the dominant-negative effect of this mutation, related to a defective N-terminal. [224,225] Several N-terminal variants, including R104W and R121W, and the mutated protein Y87C were overexpressed in human kidney TsA-201 and COS-7 cell lines. Mutant proteins showed binding to calmodulin (weak for R121W variant) and wild-type Nav1.5 channels.…”
Section: Brs Due To Drug Cardiotoxicitymentioning
confidence: 99%
“…Unlike potassium channel genes, which encode one fourth of tetramers constituting functional channels, Na v 1.5 channels were thought to be structured as monomers, since the gene encodes the entire 4domain channel α-subunit. It was thus unexpected to report Na v 1.5 mutants with a dominant-negative effect on wildtype (WT) channels, i.e., a decrease of I Na exceeding the 50% of current density expected in case of haploinsufficiency observed when coexpressing some mutants with WT channels in a 1:1 ratio to mimic patient heterozygosity, as we and others did [2][3][4][5][6][7][8][9]. Furthermore, we demonstrated that Na v 1.5 α-subunits could interact with each other and that a trafficking-efficient mutant channel was able to drive a trafficking-deficient one to the surface membrane [3].…”
Section: Introductionmentioning
confidence: 66%
“…Some of these channelopathies are widely described in Section 4 of this review. Additionally, several SCN5A missenses can generate dominant-negative variants affecting Na v 1.5 trafficking or gating at the cell surface [39][40][41]. A recent study demonstrated that most of SCN5A missense that generate loss-of-function variants exert a dominant-negative effect that confers a high burden of BrS [42].…”
Section: Genetic Code Of Scn5amentioning
confidence: 99%